Amphetamine-type stimulants use and socio-economic factors associated with hepatitis C antibody positivity among border drug users in South of China - Li, Jing; Li, Minyue; Zhang, Yunjia; Li, Jiashuang; Zhao, Yinzhou; Lu, Rong; You, Jing (Frontiers in Public Health, 2022)
Background Amphetamine-type stimulants (ATS) use has become popular in China. This study explored ATS use status and related risk factors of hepatitis C virus (HCV) infection among ATS users in Jinghong City, Xishuangbanna Prefecture, Yunnan Province, China. Methods A cross-sectional study was conducted by questionnaires from January to July 2021 in border area in Yunnan. Respondent driving sampling and consecutive sampling was carried out among border drug users, and blood samples were tested for HCV antibodies. HCV infection and related risk factors among ATS users were measured. Descriptive, univariate and multivariate analysis were conducted separately by Software SPSS 26.0. Results The ATS users accounted for 85.82% (345/402) among drug users, while anti-HCV antibody prevalence was 6.38% (22/345) among ATS users. The combined use of other types of drugs (OR = 7.29, 95%CI: 1.982–26.81, P = 0.003), injection drug use (OR = 6.823, 95%CI: 1.898–24.525, P = 0.003), average monthly income (OR = 4.825, 95%CI: 1.325–17.566, P = 0.017) might increase the risk of HCV infection among ATS users. ATS users with high school or above had higher HCV infection rates than those with primary school or below (OR = 5.718, 95%CI: 1.172–27.908, P = 0.031). Conclusion Taken together, among drug users using ATS in Jinghong City, Xishuangbanna Autonomous Prefecture, Yunnan Province, combined use of multiple drugs and intravenous drug use was the high risk factor for HCV infection. Therefore, corresponding education and intervention measures should be taken.